2018
DOI: 10.14716/ijtech.v9i8.2749
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of Market Orientation on Malaysian Automotive Industry Supply Chain Performance

Abstract: The liberation of world trade has significantly reduced Malaysian government protectionism of its national automotive industry. Local manufacturers have to strive for excellence in order to be able to compete in a business world that is dominated by a few big players. They cannot compete without excellent organizational behavior and culture. One of the important aspects of organizational culture and behavior is market orientation. A company's ability to win orders depends on how much it and the other companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Some studies have found that between industrial development and regional industrial structure, the two have a high degree of coupling, and scientific and technological innovation and industrial structure upgrading are the focus of their mutual coupling, and the goal of coupling is achieved through the internal network system of industry with the support of various external forces [13]. Some researchers believe that the coupling development of strategic emerging industries and traditional industries plays an important role in the construction of the modern industrial system, the improvement of international competitiveness, and the realization of economic transformation [14]. In addition, there are also studies that strategic emerging industries and traditional industries have an interactive relationship, with the former needing the promotion of the latter at the early stage of development and the transformation and upgrading of the latter needing the drive of the former [15].…”
Section: The Related Workmentioning
confidence: 99%
“…Some studies have found that between industrial development and regional industrial structure, the two have a high degree of coupling, and scientific and technological innovation and industrial structure upgrading are the focus of their mutual coupling, and the goal of coupling is achieved through the internal network system of industry with the support of various external forces [13]. Some researchers believe that the coupling development of strategic emerging industries and traditional industries plays an important role in the construction of the modern industrial system, the improvement of international competitiveness, and the realization of economic transformation [14]. In addition, there are also studies that strategic emerging industries and traditional industries have an interactive relationship, with the former needing the promotion of the latter at the early stage of development and the transformation and upgrading of the latter needing the drive of the former [15].…”
Section: The Related Workmentioning
confidence: 99%
“…The effects of entrepreneurial attitude, subjective norm, and perceived behavior lead to the formation of intention. In this study, the entrepreneurial intention is defined as a cognitive condition that will direct individual attention and action towards self-employment [31][32][33][34][35].…”
Section: Authors Summarymentioning
confidence: 99%
“…There are many ways that companies maintain customer trust; one of them is trying to consistently fulfil the customer's demand. This goal utilizes a supply chain in many fields, such as the Malaysian automotive industry (Ashari et al, 2018), school feeding program in the Philippines (Miro et al, 2018), Malaysian public sector projects (Riazi and Nawi, 2018), etc. Supply chains rely much on inventory management.…”
Section: Introductionmentioning
confidence: 99%